Cardiovascular magnetic resonance in immune checkpoint inhibitor-associated myocarditis. (29th February 2020) - Zhang, Lili; Awadalla, Magid; Mahmood, Syed S; Nohria, Anju; Hassan, Malek Z O; Thuny, Franck; Zlotoff, Daniel A; Murphy, Sean P; Stone, James R; Golden, Doll Lauren Alexandra; Alvi, Raza M; Rokicki, Adam; et al.
Abstract: Aims: Myocarditis is a potentially fatal complication of immune checkpoint inhibitors (ICI). Sparse data exist on the use of cardiovascular magnetic resonance (CMR) in ICI-associated myocarditis. In this study, the CMR characteristics and the association between CMR features and cardiovascular events among patients with ICI-associated myocarditis are presented. Methods and results: From an international registry of patients with ICI-associated myocarditis, clinical, CMR, and histopathological findings were collected. Major adverse cardiovascular events (MACE) were a composite of cardiovascular death, cardiogenic shock, cardiac arrest, and complete heart block. In 103 patients diagnosed with ICI-associated myocarditis who had a CMR, the mean left ventricular ejection fraction (LVEF) was 50%, and 61% of patients had an LVEF ≥50%. Late gadolinium enhancement (LGE) was present in 48% overall, 55% of the reduced EF, and 43% of the preserved EF cohort. Elevated T2-weighted short tau inversion recovery (STIR) was present in 28% overall, 30% of the reduced EF, and 26% of the preserved EF cohort. The presence of LGE increased from 21.6%, when CMR was performed within 4 days of admission to 72.0% when CMR was performed on Day 4 of admission or later. Fifty-six patients had cardiac pathology. Late gadolinium enhancement was present in 35% of patients with pathological fibrosis and elevated T2-weighted STIR signal was present in 26% with a lymphocytic infiltration. Forty-one patients (40%) had MACE over a follow-up time of 5 months. The presence of LGE, LGE pattern, or elevated T2-weighted STIR were not associated with MACE. Conclusion: These data suggest caution in reliance on LGE or a qualitative T2-STIR-only approach for the exclusion of ICI-associated myocarditis.